Impact of tourniquet use on severity of snakebite envenoming in Chongqing, China: a single-center retrospective study - Yang, Qian; Gao, Yunhan; Fu, Weijie; Ma, Shaying (Journal of international medical research, 2024)
Objective To identify risk factors associated with snakebite severity and determine whether tourniquet use can affect the severity and outcome of snakebites. Methods The clinical data of patients who sustained limb snakebites from 1 March 2021 to 31 October 2022 were reviewed. The patients were divided into three groups according to snakebite severity: mild (517 cases), moderate (112 cases), and severe (8 cases). We compared the clinical data of mild versus moderate to severe snakebites. Multivariate logistic regression was used to determine the independent risk factors for moderate to severe snakebites. Results The study involved 637 patients. There were statistically significant differences in age, tourniquet use, onset time, white blood cell increase, platelet decrease, creatine kinase (CK) increase, activated partial thromboplastin time shortening, and length of stay between patients with mild snakebites and those with moderate to severe snakebites. Multivariate logistic regression analysis showed that age, tourniquet use, and CK increase were independent risk factors for moderate to severe snakebites. Conclusion The overall severity of snakebites in Chongqing is mild, and the prognosis is good. Age, tourniquet use, and CK increase are independent risk factors for the severity of snakebites. We do not recommend tourniquet use after snakebites in Chongqing.